Evaluasi Kinerja Komisi Pemilihan Umum dalam Meningkatkan Partisipasi Pemilih - Noviyati, N.; Yasin, H. M. (Fakultas Hukum, Universitas Muslim Indonesia, 2021)
This study aims to determine the General Election Commission of Bone Regency's duties and powers in implementing the General Election, especially implementing the 2019 Presidential and Presidential Election based on Law No. 7 of 2017. Besides, this study also aims to determine the factors that influence the election to be considered not optimal. This study uses empirical research methods. Data obtained directly from the object of research in the field through observations and interviews with informants. The data is processed and analyzed qualitatively. The results obtained show that the General Election Commission of Bone Regency's performance in the implementation of 2019 Presidential and Vice-Presidential Election has been going well and is implemented based on Law No. 7 of 2017. Although in general, it is assessed that the performance of the General Election Commission of Bone Regency has not reached optimal performance because it is proven that there are still problems related to the final voter list and violations of Article 372 section (2) letter d of Law No. 7 of 2017, and culminating in a Re-Voting in several sub-districts or villages in Bone Regency. The factors affecting the General Election Commission's performance have not yet reached optimal performance due to internal and external factors. Internal factors include human resources and infrastructure. Meanwhile, the external factor is still low public knowledge in the political field, especially electoral matters.